Clinical and haematological risk factors for cerebral macrovasculopathy in a sickle cell disease newborn cohort: a prospective study. (5th January 2016) - Sommet, Julie; Alberti, Corinne; Couque, Nathalie; Verlhac, Suzanne; Haouari, Zinedine; Mohamed, Damir; François, Martine; Missud, Florence; Holvoet, Laurent; Elmaleh, Monique; Ithier, Ghislaine; Denjean, André; et al.
Summary: Children with sickle cell disease (SCD) have a significant vascular morbidity, especially cerebral macrovasculopathy (CV), detectable by transcranial Doppler. This study aimed to identify risk factors for CV using longitudinal biological and clinical data in a SCD newborn cohort followed at the Robert Debre Reference centre ( n  = 375 SS/Sβ 0 ). Median follow‐up was 6·8 years (2677 patient‐years). Among the 59 children presenting with CV, seven had a stroke. Overall, the incidence of CV was 2·20/100 patient‐years [95% confidence interval (95% CI): 1·64–2·76] and the incidence of stroke was 0·26/100 patient‐years (95% CI: 0·07–0·46). The cumulative risk of CV by age 14 years was 26·0% (95% CI: 20·0‐33·3%). Risk factors for CV were assessed by a Cox model encompassing linear multivariate modelling of longitudinal quantitative variables. Years per upper‐airway obstruction [Hazard ratio (HR) = 1·47;95% CI: 1·05–2·06] or bronchial obstruction (HR = 1·76; 95% CI: 1·49–2·08) and reticulocyte count (HR = 1·82 per 50 × 10 9 /l increase;95% CI: 1·10–3·01) were independent risk factors whereas fetal haemoglobin level (HR = 0·68 per 5% increase;95% CI: 0·48–0·96) was protective. Alpha‐thalassaemia was not protective in multivariate analysis (ancillary analysis n  = 209). Specific treatment for upper or lower‐airway obstruction and indirect targeting of fetal haemoglobin and reticulocyte count by hydroxycarbamide could potentially reduce the risk of CV.